RA02.04: UTILIZATION OF ENHANCED RECOVERY AFTER SURGERY (ERAS) PROTOCOL IN PATIENTS UNDERGOING ESOPHAGEAL RESECTION: META-ANALYSIS OF RANDOMIZED TRIALS. (14th September 2018) - Triantafyllou, Tania; Singhal, Saurabh; Olson, Michael; Bhirud, Deepak
Abstract: Background: ERAS protocol for esophageal surgeries has gained recognition in the past decade with reported benefits of shortened hospital stay, quick recovery of function, improved quality of life, lower morbidity, and reduced overall cost. A meta-analysis was conducted to establish weighted-pooled analysis of current literature comparing ERAS protocol against standard management following esophageal resection. Methods: A systematic search of literature databases was completed from January-1990 to January-2018 using predetermined keywords. Inclusion criteria were randomized controlled trials (RCTs) with sample size of > 30 patients in each arm and with overlapping ERAS protocols. Primary outcome variables were mean hospital stay (days), mean time to passage of flatus (hours), bowel motion (days), and rate of anastomotic leak. Secondary outcome variables were cardiac arrhythmia, pulmonary complications and overall morbidity. Mean difference (MD) for continuous variables and Odds ratio (OR) or Risk Difference (RD) for dichotomous variables with 95% confidence interval (CI) were calculated. Between-study heterogeneity was assessed by the I 2 statistics and χ 2 Q-test. Random effect model was used for substantial heterogeneity (I 2  > 40% or P  < 0.10) and otherwise, fixed effect model was used. Results: Three RCTs were identified with a total of 358 patients (179 in each group). Hospital stay [MD = 4.47(95%CI = 2.39–6.55; P  < 0.00001; I 2  = 98%)] and time to passage of first flatus [MD = 20.56(95%CI  = 1.05–40.07; P  < 0.00001; I 2  = 99%)] were reported by all three studies and pooled analysis favored ERAS group with substantial heterogeneity. Time to first bowel motion significantly favored the ERAS group with the least heterogeneity [MD = 1.36(95%CI = 0.94–1.78; P  = 0.63; I 2  = 0%)]. All dichotomous variables showed minimal between-study heterogeneity. ERAS group showed better outcome with regards to overall morbidity [RD = 0.10(95%CI = 0.03–0.18; P  = 0.45; I 2  = 0%)], pulmonary complications [OR = 0.26(95%CI = 0.10–0.63; P  = 0.91; I 2  = 0%)] and rate of anastomotic leak [OR = 0.12(95% CI = 0.01–0.94; P  = 0.47; I 2  = 0%)]. There was no difference between the two groups for cardiac arrhythmias [OR = 0.77(95% CI = 0.19–3.18; P  = 0.32; I 2  = 0%)]. Other outcome variables of interest, including quality of life, patient satisfaction, hospital cost, and in-hospital or 30-day mortality were inadequately reported by studies to be amenable to pooled analysis. Conclusion: ERAS protocol shows significant improvement in post-operative recovery and lower complication rates as compared with standard management, without any increase in anastomotic leak rate. However, variability and discrepancy in protocols followed by different institutions is noteworthy. Establishment of standardized ERAS protocols is warranted. Disclosure: All authors have declared no conflicts of interest.